IS MIGRATION AT OLDER AGE ASSOCIATED WITH POORER MENTAL HEALTH: EVIDENCE FROM CHINESE OLDER IMMIGRANTS IN THE UNITED STATES. (11th November 2018) - Guo, M; Stensland, M; Li, M; Dong, X
Abstract: This study addressed two questions: Is migrating at older age associated with poorer mental health? If so, what factors account for such differences? Using data of 3, 138 Chinese elderly in Chicago, we compared level of depression and quality of life among individuals who migrated in young-adulthood, adulthood, midlife, and later life, and examined whether and in what ways four sets of explanatory variables (family/social relations, socioeconomic status, health status, acculturation level) contribute to potential group differences. Results of negative binominal regressions showed that migrating in later life was associated with more depressive symptoms, possibly due to weaker social relations, lower income, and lack of access to health care among late-life immigrants. However, regardless of the explanatory variables, migrating at middle age was associated with lower quality of life. The findings revealed heterogeneity among older immigrant populations and point to the key role of family and social relations in their well-being.